Development of Canva-Based E-Module on Biotechnology Subject for 10th Grade High School Students - Rahma, Syifa Aliya; Sulistiyawati, Sulistiyawati (Proceeding International Conference on Religion, Science and Education, 2024)
Biotechnology is complex and applicable material but is difficult for students to understand due to limitations in schools in the form of less attractive learning media. This study aims to determine the development, quality and response of students to e-modules based on Canva in class 10th SMA/MA biotechnology material. This research method is Research and Development (R&D) with the ADDIE model which is used up to the Development stage. The quality test involved 1 material expert, 1 media expert, 10 peer reviewers, and 1 biology teacher, with an assessment of 95.32% and a very good category. The student response test involved 35 students, with an assessment of 82.48% and the category strongly agreed. As a result, the Canva e-module for the tissue culture and vaccine sub-material in Biotechnology material in class 10th SMA/MA was successfully developed. This e-module has very good quality and student response, worthy of being used as a medium for learning biology in biotechnology material.